The antibacterial arm of the Drosophila innate immune response requires an IkappaB kinase. - Lu, Y.; Wu, L.P.; Anderson, K.V. (Genes & Development, 2001)
The ird5 gene was identified in a genetic screen for Drosophila immune response mutants. Mutations in ird5 prevent induction of six antibacterial peptide genes in response to infection but do not affect the induction of an antifungal peptide gene. Consistent with this finding, Escherichia coli survive 100 times better in ird5 adults than in wild-type animals. The ird5 gene encodes a Drosophila homolog of mammalian IkappaB kinases (IKKs). The ird5 phenotype and sequence suggest that the gene is specifically required for the activation of Relish, a Drosophila NF-kappaB family member.